1999
DOI: 10.1007/s003300050843
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic variation in the origin of the main renal arteries: spiral CTA evaluation

Abstract: The aim of this study was to provide quantitative data on the origin and trajectory of the main renal arteries using spiral CT angiography and arteriography. Normal renal artery anatomy was assessed on spiral CT angiography (axial transverse sections and shaded-surface-display reconstructions) in 100 patients referred for renal arteriography who had no significant renal artery stenosis. Two hundred major renal arteries were studied. The vast majority of right (88 %) and left (87 %) renal arteries originated be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 9 publications
7
45
1
Order By: Relevance
“…It has been reported that in 17% and 22% renal arteries originated from the level of L1-L2 intervertebral disc on the right side and in 23% and 22% renal arteries originated from the level of L1-L2 intervertebral disc on the left side. 10,15 These findings in this study could be considered as moderate.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It has been reported that in 17% and 22% renal arteries originated from the level of L1-L2 intervertebral disc on the right side and in 23% and 22% renal arteries originated from the level of L1-L2 intervertebral disc on the left side. 10,15 These findings in this study could be considered as moderate.…”
Section: Discussionmentioning
confidence: 54%
“…6,13,14 The successful implantation of a renal stent also requires precise knowledge of the origin of the renal arteries from the aorta. 15 ERAs usually enter the upper or lower poles of the kidney and lower Table 1. Distribution of renal arteries according to the level of origin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous anatomic, conventional angiographic and CT angiographic reports concerning the renal artery have been typically morphometric studies and have usually investigated the prevalence of an aRA (1,10,15,16). The prevalence of an aRA has been generally accepted to be approximately 25-30% in different study series (1-4, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Its origin is the abdominal aorta, between the levels of L1 and L2 [1][2][3] . According to Testut and Latarjet 4 , the right renal artery in adults presents the path of about 5 cm, and the left approximately 7 cm.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%